Bias Gender dalam Iklan Lowongan Pekerjaan: (Studi pada Akun Instagram @openkerja, @loker.id, dan @lokerind) - Anggita, Safira Dea (Paradigma, 2022)
One of the problems currently being faced by Indonesia is unemployment. In order for the entire working age population to have equal opportunities to get a job, job opportunities must be able to meet these needs without any discrimination. But in reality, a lot of job advertisements on Instagram still ask for certain gender requirements even though these conditions are not relevant to the roles of the job being offered. The purpose of this study is to understand the division of labor between men and women in work and to analyze forms of gender bias in the labor recruitment process. This research is a qualitative research using Roland Barthes’s semiotic approach. The results of this study show that there are differences in the characteristics of job advertisements for women and men. Most of the jobs offered to women are in the hospitality sector, while all jobs for men are related to company facilities, infrastructure, and management. More managerial positions are also offered to men. Images on job advertisements for women show the impression that this type of work is mostly indoors and requires a friendly attitude. Whereas in the job vacancy advertisements for men, the image shows the types of jobs that are mostly in the field. In addition, there are differences in criteria related to age limit, education level, marital status, soft skills and hard skills, physical condition, and preferences for location and work time distribution system. Keywords: Gender Bias; Job Advertisements; Gender Inequality; Gender Role; Social Media.